Pengaruh Brand Awareness dan Brand Image Terhadap Niat Bersalin di Klinik Utama Familia Kabupaten Sikka, Nusa Tenggara Timur dengan Persepsi Nilai sebagai Variabel Mediasi - Natalia Regina; Kartika Imasari Tjiptodjojo (Dinasti Review, 2026)
This study aims to analyze the influence of brand awareness and brand image on birth intention at the Familia Main Clinic in Maumere, with perceived value as a mediating variable. The study involved 100 respondents who were expectant mothers or women of productive age who were familiar with the Familia Clinic, analyzed using PLS-SEM. The results obtained showed that brand awareness influenced birth intention. Conversely, brand image did not show a significant direct influence on birth intention. Furthermore, perceived value was proven to have an influence on birth intention and was the most dominant variable in the research model. Perceived value partially mediates the relationship between brand awareness and birth intention and fully mediates the relationship between brand image and birth intentions. These findings indicate that expectant mothers' decisions in choosing a birth facility are more influenced by the perceived value of the service than by brand image alone. Therefore, clinic managers need to strengthen marketing strategies oriented towards increasing patient benefits through service quality, facility comfort, and positive service experiences.